Strategi Pentahelix Badan Nasional Penanggulangan Terorisme dalam Menurunkan Potensi Radikalisme di Indonesia - Dedi Kurnia; Mhd Halkis; David Yacobbus (CV. AFDIFAL MAJU BERKAH, 2023)
Radicalism in Indonesia, particularly when claiming to represent Islam, is driven by socio-historical, political, economic, social, and cultural factors that are exploited by terrorist groups to manipulate Muslims on a global scale. Such radicalism has led to various criminal acts that have shaken Indonesia, especially since the reform era, disrupting the safety and well-being of its people. The factors contributing to radicalism's emergence include a lack of accurate religious understanding, dogmatic interpretations, and strict religious prohibitions. Inadequate knowledge of history and sociology also plays a role. The government has taken steps in counterterrorism, including establishing the National Counterterrorism Agency (BNPT) and Densus 88 Anti-Terror. Legal and institutional measures are crucial in confronting terrorism threats. The